Insights into the elimination mechanisms employed for the degradation of different hexachlorocyclohexane isomers using kinetic isotope effects and docking studies. (10th July 2013) - Manna, Rabindra Nath; Dybala‐Defratyka, Agnieszka
Abstract : Modern DFT functional as well as the continuum solvation model have been applied in order to theoretically predict carbon, chlorine and hydrogen kinetic isotope effects (KIEs) during aerobic degradation of four hexachlorocyclohexane isomers (α, β, δ and γ). A small model of the hexachlorocyclohexane dehydrochlorinase (LinA) active site comprising its catalytic dyad has been constructed based on the receptor–ligand complexes suggested by docking studies and compared to the respective reaction modeled in aqueous solution. In‐depth analysis of chlorine and hydrogen KIEs patterns clearly indicates different transition states in aqueous solution and in the model mimicking the protein active site. Although all isomers seem to undergo a concerted E2 mechanism, the contribution of proton transfer and carbon–chlorine leaving group bond stretch in the transition states differs for the different isomers giving rise to totally different magnitudes of predicted isotope effects. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Superimposed structures of the transition states and primary 37 Cl‐KIEs obtained at the PCM/M05‐2X/6‐31+G(d, p) (W model) and M05‐2X/6‐31+G(d, p) (HD model) levels of theory for the first degradation step of α‐HCH, β‐HCH, δ‐HCH, and γ‐HCH are shown in the table of contents.